In silico analyses of Wilms׳ tumor protein to designing a novel multi-epitope DNA vaccine against cancer. (21st August 2015) - Khalili, Saeed; Rahbar, Mohammad Reza; Dezfulian, Mohammad Haj; Jahangiri, Abolfazl
Abstract: Predefined and pre-weighted objective criteria and essential role of Wilms׳ tumor wild type gene (WT1) for maintaining transformed features of cancer cells confirm the high potency of WT1 as a valuable cancer antigen. The antigen was at the top of the ranking among 75 representative cancer antigens. In the present study, an in silico approach was launched to characterized novel CTL epitopes and design a novel multi-epitope DNA vaccine to elicit a desirable immune response against cancers over expressing WT1. Forty-four novel epitopes were described. A multi-epitope construct was designed based on predicted epitopes which is 310 residues in length. The vaccine candidate designed here displays acceptable population coverage (>65%) in different ethnicities as well as high probability of eliciting WT1 antibodies which both are pertinent goals in the context of appropriate multi-epitope vaccines. Various in silico analyses indicate that final vaccine is a qualified immunotherapy candidate capable of eliciting both CD4+ and CD8+ T cell responses. Highlights: T cell epitopes of WT1 were predicted by an integrated in silico approach. A construct was designed based on the predicted T cell epitopes. The construct was nominated as a qualified candidate for cancer immunotherapy.